Factors Affecting Income of Female Workers Producing Ketupat Casing and Their Contribution to Household Income - Siska Marwati; Dijan Rahajuni; Supadi Supadi (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2020)
This study aims to examine the effect of education level, working time, age, work experience and number of family members on income of female workers in Datar Village and measure the extent of income contribution of female workers producing ketupat casing to household income. The respondents were selected using the census method and data were analyzed using multiple linear. This study found that education level, working time, work experience and number of family members had a significant effect on income of female workers. Age had no effect on income of female workers. The variable with the strongest relationship to income of female workers was working time. The implications of this study are that in order to increase their income, the female workers should utilize the residue of ketupat casing production in the form of coconut sticks to make other handicrafts, such as woven plates and broom sticks. The crafts can be sold in order to increase income of female workers producing ketupat